Evaluation of the spouted bed dried leaf extract of Bauhinia forficata for the treatment of experimental diabetes in rats - Pepato, M. T. [UNESP]; Conceição, C. Q. [UNESP]; Gutierres, V. O. [UNESP]; Vendramini, R. C. [UNESP]; Souza, C. R.F.; Oliveira, W. P.; Brunetti, I. L. [UNESP] (My University, 2010)
Previously, we have demonstrated that treatment of experimental diabetes with a decoction of Bauhinia forficata leaves is beneficial. In this study, we prepared a two-fold concentrate of this extract and tested its effects on physiological, biochemical and toxicity markers in streptozotocin-diabetic rats. Dried and ground leaves were extracted with warm 70% hydroethanol and the filtrate concentrated by evaporation at 50°C. This solution was mixed with colloidal silicon dioxide (Tixosil-333®) and dried in a spouted bed (BfT). Rats were treated with water, insulin and Tixosil particles at low or high doses, alone or coated with dried BfT. Animals were periodically weighed and monitored for water and food intake; urinary volume, glucose, urea and protein; blood glucose, serum lipids, liver toxicity markers transaminase and phosphatase and masses of adipose tissue and skeletal muscle. Insulin treatment gave best rat growth and lowest values for all other markers. No other treatment affected any diabetic marker, but the enzyme activities were changed by diabetes and BfT. Thus, BfT toxicity could arise from secondary products of plant constituents or Tixosil interaction. Therefore, BfT prepared in the spouted bed as described, is unsuitable for treatment of diabetes, which implies that the method of preparation of any medicine is critical for its efficacy and toxicity. © 2010 Academic Journals.
Keywords: Bauhinia forficata; Enzymes; Physiological variables; Plasma glucose; Serum lipids; Serum toxicity markers; Spouted bed drying